The Low-Volatility Anomaly in the London Stock Exchange - Koivisto, Manu (My University, 2024)
This thesis aims to examine the phenomena called the low-volatility anomaly and find evidence of its possible existence in the London Stock Exchange. The literature review part of the thesis inspects the concepts of risk and return and their evolvement in academia over the years. In addition, the relevant prior research on the low-volatility anomaly is covered, together with the explanations suggested for the low-volatility anomaly such as behavioural explanations and conflicts of interest. The empirical part of the thesis investigates the low-volatility anomaly by constructing from the constituents of the FTSE All-Shares Index various sized portfolios by each stock’s historical volatility, and later market capitalisation. The returns of these portfolios are then evaluated by using absolute returns and risk-adjusted returns more often associated with portfolio management. This thesis also includes the results for over 150 CAPM regressions done for each portfolio and a regression using market capitalisation as a control variable. The results indicate that the low-volatility anomaly does exist in the London Stock Exchange over the 2009-2023 period as lower volatility portfolios are associated with greater risk-adjusted returns.

Tämä tutkielma pyrkii tarkastelemaan alhaisen volatiliteetin anomaliaa ja etsimään todistusaineistoa sen olemassaolosta Lontoon pörssissä. Tutkielman kirjallisuuskatsauksessa tarkastelussa on riskin ja tuoton käsite sekä niiden osallisuus keskeisiin rahoitusteorioihin vuosien varrella. Kirjallisuuskatsaus sisältää myös joitain selityksiä alhaisen volatiliteetin anomalialle, kuten käyttäytymiseen tai eturistiriitoihin liittyviä ehdotuksia. Tutkielman empiirinen osa muodostaa FTSE All-Shares-indeksin osakkeista historiallisen volatiliteetin perusteella eri kokoisia salkkuja. Myöhemmin toiseksi jakamisperusteeksi tulee myös yrityksen markkina-arvo. Salkkujen tuottoa arvioidaan niin tuottojen kuin riskikorjattujen tuottojen näkökulmasta. Tutkielma sisältää myös yli 150 CAPM-regressiota eri perustein muodostetuille salkuille sekä regression, jossa yritysten markkina-arvoa pidetään kontrollimuuttujana. Tutkielman empiiriset tulokset osoittavat, että alhaisen volatiliteetin anomalia on läsnä Lontoon pörssissä ajanjaksona 2009-2023, sillä alhaisemman historiallisen volatiliteetin omaavat salkut voidaan yhdistää parempiin riskikorjattuihin tuottoihin.
Keywords: low-volatility anomaly, risk and return, modern portfolio theory, efficient market hypothesis, capital asset pricing model, risk-adjusted return, portfolio management, alhaisen volatiliteetin anomalia, riski ja tuotto, moderni portfolioteoria, tehokkaiden markkinoiden hypoteesi, capital asset pricing model, riskikorjattu tuotto, salkun hallinta